A Causal Inference Framework for Climate Change Attribution in Ecology - Dudney, Joan; Dee, Laura E.; Heilmayr, Robert; Byrnes, Jarrett; Siegel, Katherine (Ecology letters, 2025)
ABSTRACT As climate change increasingly affects biodiversity and ecosystem services, a key challenge in ecology is accurate attribution of these impacts. Though experimental studies have greatly advanced our understanding of climate change effects, experimental results are difficult to generalise to real‐world scenarios. To better capture realised impacts, ecologists can use observational data. Disentangling cause and effect using observational data, however, requires careful research design. Here we describe advances in causal inference that can improve climate change attribution in observational settings. Our framework includes five steps: (1) describe the theoretical foundation, (2) choose appropriate observational datasets, (3) estimate the causal relationships of interest, (4) simulate a counterfactual scenario and (5) evaluate results and assumptions using robustness checks. We demonstrate this framework using a pinyon pine case study in North America, and we conclude with a discussion of frontiers in climate change attribution. Our aim is to provide an accessible foundation for applying observational causal inference to estimate climate change effects on ecological systems. Accurately attributing ecological shifts to climate change remains a significant challenge. Here, we present an accessible causal inference framework designed for climate change attribution in observational settings. Using a case study and a discussion of key frontiers, we provide ecologists with robust tools to better quantify and manage ecosystem responses in a rapidly warming world.